Multiple Methods Synergistically Promote the Synchronization of Somatic Embryogenesis Through Suspension Culture in the New Hybrid Between Pinus elliottii and Pinus caribaea - Li, Fengqing; Yao, Jiabao; Hu, Lingfeng; Chen, Jinhui; Shi, Jisen (Frontiers in Plant Science, 2022)
Pinus elliottii × Pinus caribaea is an interspecific pine hybrid of major economic importance. Somatic embryogenesis and plant regeneration in Pinus elliottii × Pinus caribaea on solid medium have been reported previously; however, a current limitation is the lack of a stable and effective method for its commercial use. The objective of this study was to establish a suspension culture system and evaluate the effect of multiple methods synergistically on the synchronization of embryo development in Pinus elliottii × Pinus caribaea. For the former, a protocol to initiate and establish suspension culture system of P. elliottii × P. caribaea was presented. Based on biomass growth, the growth of somatic calli (SE) followed an S-shape curve in suspensions grown for a 15-days period and the exponential phase of cell suspensions was reached between days 3 to 6. The initial packed-cell-volumn (PCV) and revolutions per minute (rpm) has significant effect on the proliferation of EC, the highest proliferation multiple reached to 6.86 (±0.06) at the initial density of 5mL PCV under a 9–10-days transfer interval in the dark on a rotary shaker at 70 rpm. For the latter, the influence of abscisic acid (ABA), ammonium (NH4+), nitrate (NO3−), low temperature and polyethylene glycol (PEG) on somatic embryogenesis was very significant. When embryogenic calli (EC) suspended in the medium at a presence of 37.84 μM·L−1 ABA , as many as 274 mature cotyledonary embryos per mL PCV of cells were thereafter formed in the mature medium, and 266 somatic embryos were obtained on mature medium after suspension culture in liquid medium containing 10 mmol·L−1 NH4+ and 30 mmol·L−1 NO3−. Furthermore, reducing the concentration of 2,4-D gradually and 4°C incubation for 12 h in the initial of exponential phase could promote the synchronization of somatic embryogenesis, which resulted in 260 mature cotyledonary embryos. This suspension culture system and method of synchronic control can be used in large-scale production of P. elliottii × P. caribaea seedlings.